HUMAN RESOURCE MANAGEMENT STRATEGIES IN IMPROVING EMPLOYEE PERFORMANCE IN BANDUNG CITY - Ade Mubarok (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
Human Resource Management (HRM) has become a strategic issue in improving employee performance within public sector organizations, particularly in local government institutions facing increasing demands for effective and high-quality public services. However, governmental institutions in Bandung City still encounter several challenges, including low employee discipline, inadequate competencies, weak work motivation, and ineffective performance management systems. This study aims to analyze the implementation of HRM strategies in improving employee performance in governmental institutions in Bandung City. The research specifically addresses the question of how HRM strategies, including training and development, work motivation, performance appraisal, compensation systems, and career development, contribute to employee performance enhancement. This study employs a qualitative descriptive approach using interviews, observations, questionnaires, and documentation as data collection techniques. The collected data were analyzed through descriptive qualitative analysis supported by percentage calculations based on a Likert scale. The findings reveal that HRM strategies significantly contribute to improving employee productivity, professionalism, discipline, and organizational commitment. Among the examined dimensions, training and development emerged as the most influential factor in enhancing employee competencies and adaptability, particularly in the era of digital public service transformation. Furthermore, fair compensation systems, transparent performance evaluations, and merit-based career development positively affect employee motivation and organizational effectiveness. This study contributes academically to the development of HRM studies within the context of public sector organizations and provides practical recommendations for policymakers in designing more effective employee management systems to improve public service quality and organizational performance.